The Utilization of Unused Paddy Lands in Negeri Sembilan - Thiran, Nyanen (1981)
Non -utilization of alienated paddy lands in Negeri Sembilan had posed serious problems to the State a s well as the Federal Government. The State h as approximately 36,456 acres of gazetted paddy land but only 43 per cent of the area a re cultivated and utilized for paddy while the remaining 57 per cent are left idle. The broad objectives of this study are (1) to determine the factors, both economic and non-economic, that influenced farmers' decisions to leave their paddy lands idle, and (2) to formulate an alternative land use strategy with in existing re source constraints. By means of log it analysis, it was reveal ed that shortage of labour, low productivity of paddy land, high off-paddy farm income, shortage of water supply and multiple land ownership were the significant variables that influenced farmers' decision to abandon their paddy lands. A linear programming analysis, which was used to formulate the alternative land use strategy, indicates that the idle paddy lands can be economically utilized with the available resources and Government assistance. The plan as a whole advocates the adoption of an activity mix comprising of chilliest, greanpeas, maize or sugarcane cultivation and the raising of cows or freshwater fish. The actual activity mix depends mainly on the acreage to be ope rated. The stability of the linear planning model was tested through a sensitivity analysis and it was established that the linear planning model was practical, stable, financially and economically feasible to the paddy farmers. The study recognizes the potential problems that may arise from increased production of the selected commodities if the plan were to be implemented. Hence, it is recommended that further research be undertaken in the area of marketing and processing to complement the above study.